Association between burnout and sense of coherence among speech and language therapists: an exploratory study in Italy - Galletta, Maura; Portoghese, Igor; Frau, Nicola; Pau, Marco; Meloni, Federico; Finco, Gabriele; Contu, Paolo; Campagna, Marcello (Acta Biomedica Atenei Parmensis, 2019)
Background and aim: Job burnout has been recognized as a serious occupational hazard among professionals, such as health care professionals. The sense of coherence (SoC) is deemed to be a personal resource capable of reducing the impact of job stressors and, consequently, the experience of job burnout. The purpose of this study was to investigate the relationship between SoC and job burnout among speech and language therapists. Materials and methods: A descriptive and cross-sectional analysis was carried out through an online self-reported questionnaire. A total of 217 Italian speech and language therapists were involved in the study. The Anova test, T-test and logistic regression were performed to study the association between SoC and job burnout. Results: The Anova test showed that job tenure was not associated to job burnout. The T-test showed that speech and language therapists having a low SoC exhibited significantly higher emotional exhaustion, higher cynicism, and lower professional efficacy (t=-7.190 d.f.=215 p